SIMULTANEOUS INTERPRETING USED IN “THE SAMSUNG GALAXY S24 AUTOMATICALLY TRANSLATES CALLS VIA AI” VIDEO ON RAPPLER’S YOUTUBE CHANNEL - Kurnia Septiana Putri; Ramadan Adianto Budiman (Acceleration: Multidisciplinary Research Journal, 2024)
The existence of this scientific article aims to provide a brief description of the position of translation in the phenomenon of globalization, which is inseparable from technological advances and human mobility that demand a connection between language and culture. Therefore, to discuss the world of interpreting further, the researcher chose the title "Simultaneous Interpreting Used in "The Samsung Galaxy S24 Automatically Translates Calls Via AI" Video on Rappler's YouTube Channel". This research focuses on finding the modes of interpreting used with a descriptive qualitative method, and the data obtained comes from conversations between a person and AI (Artificial Intelligence) in one of Rappler's YouTube Channel videos, namely "The Samsung Galaxy S24 Automatically Translates Calls Via AI".  After the research was conducted, it was found that one interpreting mode was used based on the theory of Pochhacker, namely simultaneous interpreting, because the Live Translate feature released by the Samsung Galaxy S24 Series brand translates in real time and there are 24 conversations that can be delivered in one time or one breath but as if a pause was made therefore the AI ​​Interpreter could use that time to translate.